Phosphosulindac (OXT-328) prevents and reverses chemotherapy induced peripheral neuropathy in mice - Basu, Aryah; Yang, Jennifer Y.; Tsirukis, Vasiliki E.; Loiacono, Andrew; Koch, Gina; Khwaja, Ishan A.; Krishnamurthy, Mahila; Fazio, Nicholas; White, Emily; Jha, Aayushi; Shah, Shrila; Takmil, Cameron; et al. (Frontiers in Neuroscience, 2024)
.